Multilevel Governance, Place‐Based Policy Integration and Territorial Public Value: Developing an Integrated Analytical Framework for SDG 5 and SDG 8 Localization Through the Lombardy Case - Glauco Galati (Sustainable Development, 2026)
ABSTRACT How do multilevel governance architectures shape the localization of global sustainability objectives at the subnational level, and under what conditions does policy integration generate measurable territorial public value? This article addresses these questions through the development and empirical application of an integrated analytical framework—connecting multilevel governance (MLG) theory, place‐based policy integration, territorial public value (TPV), and the capability approach—to the case of Lombardy's implementation of SDG 5 (gender equality) and SDG 8 (decent work and economic growth). Lombardy offers a theoretically productive case: it is Italy's most economically significant region, a first‐mover on gender equality certification (the first Italian region to invest in the UNI/PdR 125 certification system with €10 million in FSE+ resources), and a documented instance of both governance successes and institutional barriers in SDG localization. Drawing on secondary data from ISTAT, Assolombarda, Regione Lombardia, and the CNEL Working Group Report on School‐to‐Work Transition (2025), the article makes three contributions. First, it operationalizes the MLG → policy integration → TPV → capability outcome chain as a testable analytical framework applicable to regional SDG localization. Second, it identifies a systematic formal‐substantive gap: Lombardy's formal governance mechanisms for SDG 5 and 8 are more developed than regional outcomes on key indicators suggest—revealing that institutional design is necessary but insufficient without conversion factors that translate formal commitments into substantive territorial capabilities. Third, it identifies four governance mechanisms through which formal SDG commitments generate or fail to generate territorial public value: vertical policy coherence, horizontal stakeholder integration, data‐driven monitoring, and evaluative accountability. Implications for regional governance reform and SDG localization theory are discussed.